2008
DOI: 10.1111/j.1399-0039.2008.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of haematopoietic stem cell transplantation in patients transplanted with matched unrelated donors vs allele‐mismatched donors: a single centre study

Abstract: We studied the importance of human leucocyte antigen (HLA)-A, -B and -DRB1 high-resolution matching on the outcome of haematopoietic stem cell transplantation (HSCT) with matched unrelated donors (MUDs) vs single allele-mismatched unrelated donors. Fifty consecutive HSCT patients receiving an HLA-A, -B or -DR allele-level-mismatched unrelated graft (mmUD) were compared with a matched cohort of 100 patients with an HLA-A, -B and -DR-MUD. Rejection occurred in seven patients (14%) in the mmUD group and in four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Park et al retrospectively analyzed a large group of patients (N=142, including 109 patients with hematologic malignancies and 33 patients with non-malignant diseases; all the patients belonged to the pediatric age group [≤18 years old]) who had undergone URD HSCT, and all HSC donors and patients were fully typed for HLA-A, HLA-B, HLA-C, and HLA-DR by using high-resolution molecular typing (4-digit level). Park et al suggested that increased numbers of HLA Mms were associated with reduced overall survival, increased risk of grade III-IV aGVHD, and greater TRM risk, thus confirming the results of many other studies [5-7]. Other important observations included that a single locus Mm at HLA-B or HLA-C was associated with significantly lower survival compared to the survival of patients with 8/8 allele match or a single Mm at HLA-A or DR; these results vary in American and Japanese reports.…”
supporting
confidence: 68%
See 3 more Smart Citations
“…Park et al retrospectively analyzed a large group of patients (N=142, including 109 patients with hematologic malignancies and 33 patients with non-malignant diseases; all the patients belonged to the pediatric age group [≤18 years old]) who had undergone URD HSCT, and all HSC donors and patients were fully typed for HLA-A, HLA-B, HLA-C, and HLA-DR by using high-resolution molecular typing (4-digit level). Park et al suggested that increased numbers of HLA Mms were associated with reduced overall survival, increased risk of grade III-IV aGVHD, and greater TRM risk, thus confirming the results of many other studies [5-7]. Other important observations included that a single locus Mm at HLA-B or HLA-C was associated with significantly lower survival compared to the survival of patients with 8/8 allele match or a single Mm at HLA-A or DR; these results vary in American and Japanese reports.…”
supporting
confidence: 68%
“…An HSCT donor is referred to as a "10/10 allele match" or "perfect match" when both HLA alleles are identical at each of the HLA-A, HLA-B, HLA-C, HLA-DRB1, and HLA-DQB1 loci. While searching for an unrelated donor, high-resolution (4-digit) genetic typing of both the patient and the donor is necessary [4, 5]. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For the remaining two thirds of the patients a donor may be available through the international donor registries. A full HLA match (10/10) is desirable when searching for a donor but some HLA-mismatches may be accepted for certain patients on an individual basis (14,15). Other important factors usually kept in mind included cytomegalovirus (CMV) status, gender, age of donor and recipient and sometimes ABO-blood group.…”
Section: Hla and Transplantationmentioning
confidence: 99%